Triglycerides and blood pressure in relation to circulating CD34-positive cell levels among community-dwelling elderly Japanese men: a cross-sectional study - Yuji Shimizu; Shimpei Sato; Yuko Noguchi; Jun Koyamatsu; Hirotomo Yamanashi; Mako Nagayoshi; Koichiro Kadota; Shin-Ya Kawashiri; Yasuhiro Nagata; Takahiro Maeda (Komiyama Printing Co. Ltd, 2017)
Abstract Background Triglycerides are reported to be positively associated with blood pressure (both systolic and diastolic). However, in a previous study, we reported a significant positive association between triglycerides and circulating CD34-positive cells (endothelial repair) among non-hypertensive, but not hypertensive, participants. Since hypertension and endothelial dysfunction have a bi-directional association (vicious cycle), the status of circulating CD34-positive cells may influence the association between triglycerides and hypertension. Methods Since antihypertensive medication use may influence results of the present study, we conducted a cross-sectional study of 327 community dwelling elderly (aged 60-69 years) Japanese participants who were not taking anti-hypertensive medication and who had participated in a general health check-up in 2013-2015. Results Participants were classified into two groups based on median values of circulating CD34-positive cells (0.93 cells/μL). For participants with lower circulating CD34-positive cells (n = 165), a significant positive association was seen between triglycerides and blood pressure, but not for participants with higher circulating CD34-positive cells (n = 162). The multivariable standardized parameter estimates (β) and p values of systolic blood pressure and diastolic blood pressure were 0.23 (p = 0.007) and 0.18 (p = 0.036) for participants with lower circulating CD34-positive cells and 0.08 (p = 0.409) and 0.03 (p = 0.786) for those with higher circulating CD34-positive cells. Conclusion A significant positive association between triglycerides and blood pressure exists among those with lower, but not higher, circulating CD34-positive cells. The level of circulating CD34-positive cells acts as a determinant factor for the association between triglycerides and blood pressure.